Criminal Law Measures to Combat Violent Crimes: International Experience and National Trends - ZHOLZHAXYNOV, Zhandos Bahtybaevich (Journal of Advanced Research in Law and Economics, 2018)
The article is devoted to criminal law measures to resist criminal abuses related to violence. In modern society, the protection of individual rights and freedoms is one of the most important tasks. Within this task, the most critical issue is that of protection of the individual from criminal violence by criminal law measures. The problems of violent crime, despite all measures taken by the state and society, do not go into the past, but become relevant for modern society. Without exaggeration, they represent a social disaster that threatens the security of the individual, society and the state. The purpose of the article is to analyze the criminal law methods of combating violent crime, to study the criminal provisions relating to the use of violence in Kazakhstan's national criminal legislation and legislation in a number of foreign countries. The article examines the opinions of scientists on the nature and characteristics of criminal violence, the criminal law of Kazakhstan and the legislation of a number of foreign countries in terms of violent crimes, formulates conclusions and sets out the recommendations for the further improvement of the criminal protection of the individual against violent endeavors. On the basis of an examination of the theoretical material and experience of foreign countries in the field of countering violent crime, the author suggested ways of counteracting the mentioned crime, suggesting further improvement of the criminal legislation of the Republic of Kazakhstan, in the sphere of protecting the individual from criminal violence. The main provisions and conclusions of the article can be used in science and practice in addressing crime prevention, comparative characteristics of the criminal regulations regarding violence in Kazakhstan and foreign countries, as well as the subsequent reform of the criminal law in the field of the physical integrity of the individual.